FAD DIETS: what is true about fad: WHAT IS TRUE ABOUT FAD? - Taus, Marina; Mignini, Elsa Veronica; Busni, Debora; Fumelli, Daniele; Vignini, Arianna; Nicolai, Giulia; Nicolai, Albano (Progress in Nutrition, 2021)
Balanced, hypocaloric diet in association to a more active lifestyle and/or bariatric surgery are the only solutions that really work against the alarming increase in overweight and obesity rates. However, overweight patients often relay on alternative, naive strategies and methods in attempt to fix their condition quickly.Fad diets are defined as weight loss strategies that promise quick results, usually promoted as not requiring physical exercise or efforts and focusing on totally unbalanced meal plans.One of the most appealing method of fad diets is the drastic reduction of carbohydrate intake, which can be acceptable but has also its “dark side”.Modifying the proportion of nutrient percentages in favor of protein intake or remarking hypothetical effects on body detoxification are typical approaches of those who promote fad diets. While some data are available on the first strategy, the scientific literature does not recognize the necessity of the body to be “detoxified” nor the existence of special meal plans/food able to do that.Trying to lose weight following a fad diets determine not only achieving a temporary result but also falling into nutritional deficiency and other health risks.Proper, balanced nutrition and physical activity are costless, effective and sustainable in the long term and should be strongly recommended to obese and overweight.